PHARMACOECONOMIC ASPECTS OF TREATMENT WITH THE INHIBITORS OF TUMOR NECROSIS FACTOR OF THE CHRONIC UVEITIS REFRACTORY TO THE BASIC THERAPY (INCLUDING AN ASSOCIATED WITH JUVENILE IDIOPATHIC ARTHRITIS) - A.V. Rudakova (Union of pediatricians of Russia, 2011)
Therapy of chronic uveitis refractory to the basic treatment, in juvenile idiopathic arthritis (JIA) is a very complex problem in pediatrics. Substantial progress in this area resulted after the implementation in practice of inhibitors of tumor necrosis factor (TNF), as the most effective in such clinical situation drugs adalimumab and infliximab are considered (although infliximab was not officially approved in JIA). Objective. To estimate the cost effectiveness of TNF inhibitors - adalimumab, and infliximab in chronic uveitis, refractory to the basic therapy (including associated with juvenile rheumatoid arthritis). Methods. A modeling on the basis of a comparative prospective cohort clinical study was carried out. The analysis was performed by the method «cost-effectiveness» from a position of health and social accounting perspective. Results. It was shown that the frequency and time of remission did not differ when treatment with infliximab (5 mg/kg at 0-2-6 weeks and further once in 6-8 weeks) and adalimumab (24 mg/m2 once in 2 weeks). Adalimumab provides a long-term maintenance of remission (no recurrence in 60% of patients within 40 months of observation), whereas 1 year after the treatment with infliximab the frequency of exacerbations was returned to that observed before therapy. The proportion of patients without relapse in the treatment with infliximab for 40 months was 18.8%. Similar results were obtained in a subset of patients with chronic uveitis associated with JIA (with follow-up of 20 months of in a group of infliximab number patients without relapse was 11.1%, with adalimumab therapy - 63.6%). In the general population of patients with refractory chronic uveitis the factor «cost-effectiveness» calculated for a patient with the maintenance of remission for 3 years with adalimumab therapy was in 2,1-2,8 times less than in the treatment with infliximab. In chronic uveitis associated with JIA, the coefficient of difference «cost-effectiveness» calculated for a patient with the maintenance of remission for 20 months was even more pronounced and was 3,9-5,1 times in favor of adalimumab. Conclusions. The realized pharmacoeconomic analysis suggests the feasibility of adalimumab treatment of chronic uveitis refractory to routine therapy. At the same time be aware that the results of the study are preliminary in nature, as they are based on data from a cohort study, which included a small number of patients.Key words: chronic uveitis, juvenile idiopathic arthritis, infliximab, adalimumab, cost-effectiveness analysis.